Manajemen Strategik dalam memberikan Pelayanan Bimbingan Manasik terhadap Calon Jemaah Haji Tahun 2023 (Studi Kasus Kantor Urusan Agama Kecamatan Ciparay) - Sambada, Reksa Adib; Muhtarom, Mumuh; Yuningsih, Yuyun (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2023)
The purpose of this study was to determine the planning, implementation, and evaluation of services to pilgrims at the Ciparay Religious Affairs Office. The theory used in this research is strategic management theory. This research uses a qualitative approach. The results showed that there are several important factors that can make Hajj ritual guidance services to prospective pilgrims more effective, which include good strategic management that is very important to plan a comprehensive Hajj guidance program, the quality of mentors, structured guidance planning, and periodic evaluation of the guidance program to identify weaknesses and prevent future mistakes. By paying attention to these factors, it is hoped that Hajj ritual guidance can help prospective pilgrims prepare well and undergo the Hajj pilgrimage in accordance with Islamic teachings.